X-band inverse class-F GaN internally-matched power amplifier *Project supported by the National High Technology Research and Development Program of China (Grant No. 2015AA016801). (2nd August 2016) - Zhao 赵, Bo-Chao 博超; Lu 卢, Yang 阳; Han 韩, Wen-Zhe 文哲; Zheng 郑, Jia-Xin 佳欣; Zhang 张, Heng-Shuang 恒爽; Ma 马, Pei-jun 佩军; Ma 马, Xiao-Hua 晓华; Hao 郝, Yue 跃
Abstract: An X-band inverse class-F power amplifier is realized by a 1-mm AlGaN/GaN high electron mobility transistor (HEMT). The intrinsic and parasitic components inside the transistor, especially output capacitor C ds, influence the harmonic impedance heavily at the X-band, so compensation design is used for meeting the harmonic condition of inverse class-F on the current source plane. Experiment results show that, in the continuous-wave mode, the power amplifier achieves 61.7% power added efficiency (PAE), which is 16.3% higher than the class-AB power amplifier realized by the same kind of HEMT. To the best of our knowledge, this is the first inverse class-F GaN internally-matched power amplifier, and the PAE is quite high at the X-band.